تحسين أداء خوارزمية الجدولة EDHS على المهام الدورية وشبه الدورية في نظم الزمن الحقيقي متعددة المعالجات - محمد حجازية; رلى مريشة (Tishreen University, 2018)
يقدم البحث طريقة جديدة لتحسين أداء خوارزمية الجدولة EDHS (الزمن الحرج الأقصر والتقسيم الأعلى أولوية) على كل من المهام الدورية وشبه الدورية في أنظمة الزمن الحقيقي متعددة المعالجات، حيث تعتبر هذه الخوارزمية من أهم خوارزميات الجدولة في الزمن الحقيقي لقدرتها على حل مشكلة الجدولة الجزئية وشبه الجزئية. شملت هذه الدراسة جدولة مهام دورية وشبه دورية ذات قيود زمنية مساوية لدورها، ومستقلة، و قابلة للمقاطعة (للتقطيع المانع-المنع) على عدة معالجات متجانسة، وتمت عملية تحليل الأداء بحساب معدل نجاح الجدولة وعدد المقاطعات وعدد الهجرات وتبديلات السياق وزمن انتظار المهام في الأرتال. تم الحصول على نتائج تطبيق هذه الخوارزمية لأول مرة على المهام الدورية وتمت مقارنة أداءها عند تطبيقها على المهام شبه الدورية، حيث يقترح البحث طريقة لتعديل عمل هذه الخوارزمية تساعد في تحسين أدائها. The paper presents a new approach to improve the performance of EDHS scheduling algorithm (Earliest Deadline and Highest Priority Split ) for periodic and sporadic tasks on real time multiprocessor systems. EDHS is one of the most important algorithms in real time multiprocessor systems and that for its ability to solve the problem of partitioning and semi-partitioning scheduling. This paper considers the scheduling of n periodic and sporadic , in-depended, and preempted tasks with implicit deadlines on a platform of m homogenous multiprocessor, and the performance analysis has been done by calculating the success rate, preemption count, migration count, the number of context switches, and tasks' average waiting time in queues. The results of EDHS algorithm on periodic tasks have been obtained for the first time, and it has been compared with sporadic ones, then the paper suggests a new approach to modify EDHS scheduling way that helps to improve the performance of EDHS.